2018
DOI: 10.4236/oalib.1103978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Striga Trap Crops and Nitrogen Fertilizer Application on Yield and Yield Related Traits of Sorghum [Sorghum bicolor (L.) Moench] at Fedis District, Eastern Ethiopia

Abstract: Striga causes a serious threat to successful cultivation of sorghum in areas of low and erratic rainfall and poor soil fertility. Therefore, to reduce yield losses and severity of Striga, a field experiment was conducted during the cropping season of 2015 on heavily Striga-infested field in Fedis District, Boko site to determine the effect of trap crops (cowpea, soybean, desmodium, control) and N fertilizer rates (0, 46, 92 and 138 kg N ha −1 ) on management of Striga, yield related traits and yield of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…If farmers can afford both inputs for all their maize fields, they will enhance maize production and build off Striga infestation faster. Optimizing the choice of crop variety and nutrient management is a common notion among integrated approaches for preventing Striga parasitism and increasing yields (e.g., Midega et al, 2014 ; Tadesse et al, 2018 ; Abdullahi et al, 2022 ). Knowledge about the effectiveness of individual and combined practices under varying conditions, as drawn from this study, is crucial to guide such decision processes.…”
Section: Discussionmentioning
confidence: 99%
“…If farmers can afford both inputs for all their maize fields, they will enhance maize production and build off Striga infestation faster. Optimizing the choice of crop variety and nutrient management is a common notion among integrated approaches for preventing Striga parasitism and increasing yields (e.g., Midega et al, 2014 ; Tadesse et al, 2018 ; Abdullahi et al, 2022 ). Knowledge about the effectiveness of individual and combined practices under varying conditions, as drawn from this study, is crucial to guide such decision processes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that application of N in four splits significantly lowered the density and dry weight of weeds. Tadesse et al [84] reported that application of N up to 46 kg ha -1 significantly reduced the density of striga, 49.8 per cent over control. Chavan et al [57] observed that four splits of nitrogen application i.e.…”
Section: (C) Cultural Methodsmentioning
confidence: 99%
“…Crops such as cotton, soybean, sunflower, cowpea, jute, pigeon pea, chickpea, kenaf, groundnut and castor will act as trap crop. Tadesse et al (2018) observed that among the trap crops, cowpea had more profound effect on suppressing the germination of striga. Cotton crop as trap crop led to a suicidal germination of 13-50 per cent striga seed (Barberi, 2019).…”
Section: Trap Croppingmentioning
confidence: 97%
“…It was also observed that application of N in four splits significantly lowered the density and dry weight of weeds. Tadesse et al (2018) reported that application of N up to 46 kg ha -1 significantly reduced the density of striga, 49.8 per cent over control.…”
Section: Fertilizationmentioning
confidence: 98%